Clinical indication of nasal surgery for the CPAP intolerance in obstructive sleep apnea with nasal obstruction. Issue 6 (December 2020) - Iwata, Noboru; Nakata, Seiichi; Inada, Hiroya; Kimura, Ayami; Hirata, Masatoshi; Yasuma, Fumihiko
Abstract: Objective: The role of isolated nasal surgery for obstructive sleep apnea (OSA) patients with nasal obstruction, especially for an intolerance for continuous positive airway pressure (CPAP), is unclear. The aim of this study was to assess the effects of surgery for OSA patients with symptomatic nasal obstruction and CPAP intolerance. Method: Retrospectve comparative study.1037 OSA patients with apnea-hypopnea index (AHI) ≥ 20 were enrolled. Case-control study was performed between the male apnea patients undergoing nasal surgery: surgery group ( n  = 43) and the pair-matched apnea patients for age, sex, body mass index, and race: control group ( n  = 43). The surgery group suffering from nasal obstruction could not use continuous positive airway pressure, and the CPAP group free from nasal obstruction could use it successfully. Results: In surgery group, surgery significantly decreased the nasal resistance and Epworth sleepiness scale scores without changing the AHI. Surgery significantly increased the nadir of oxygen saturation and shortened the apnea-hypopnea duration. Although all of the surgery group failed to use positive airway pressure preoperatively, the 40 patients of the 43 CPAP intolerance patients were able to use CPAP postoperatively. The resting three patients were cured OSA or changed the treatment to oral appliance(OA). For both groups, the cutoff nasal resistance for differentiating the failure of positive airway pressure and its success was 0.31 Pa/cm 3 /s. Conclusion: Isolated nasal surgery is effective for an intolerance of positive airway pressure in sleep apnea with nasal obstruction presumably by decreasing nasal resistance.